Poly (lactic acid-b-3-hydroxypropionic acid) block copolymer composition and film comprising same

By introducing an appropriate amount of poly(3-hydroxypropionic acid) into polylactic acid, a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition is formed, and the problem of low transparency of polylactic acid is solved and excellent Transparency and suitable membrane materials.

CN119421924APending Publication Date: 2025-02-11LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380049418.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-16
Filing Date
2023-12-15
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Polylactic acid has problems with low impact resistance, heat resistance and transparency in applications, which limits its application in food packaging and optical films.

Method used

By introducing an appropriate amount of poly(3-hydroxypropionic acid) block copolymer into polylactic acid, its physical characteristics, especially transparency, are adjusted to form poly(lactic acid-b-3-hydroxypropionic acid) block copolymer with excellent transparency, the poly(lactic acid-b-3-hydroxypropionic acid) block copolymerization is formed with excellent transparency. composition and membrane.

Benefits of technology

The low average haze of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition is achieved, which improves its transparency and is suitable for applications such as food packaging and optical films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421924A_ABST
    Figure CN119421924A_ABST
Patent Text Reader

Abstract

The present disclosure provides a poly (lactic acid-b-3-hydracrylic acid) block copolymer composition and a film comprising the same, the poly (lactic acid-b-3-hydracrylic acid) block copolymer composition comprising: a poly (lactic acid-b-3-hydracrylic acid) block copolymer and a poly (3-hydracrylic acid), in which an average haze is less than 4.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0176832 filed in the Korean Intellectual Property Office on December 16, 2022, and Korean Patent Application No. 10-2023-0182742 filed in the Korean Intellectual Property Office on December 15, 2023, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present disclosure relates to poly(lactic acid-b-3-hydroxypropionic acid) block copolymer compositions and films comprising the same. Background Art

[0004] Polylactic acid (PLA) is the resin of plant origin obtained from plants such as corn, and is concerned as the environmentally friendly material with biodegradable characteristics. Different from currently used petroleum-based resins such as polystyrene resins, polyvinyl chloride resins, polyethylene resins, etc., polylactic acid has the effect of preventing the exhaustion of resources based on petroleum and suppressing carbon dioxide emission, and therefore it can be reduced to the environmental pollution of the shortcomings of plastic products based on petroleum. Along with the environmental pollution caused by waste plastics etc. becoming a social problem, being committed to expanding the application range of polylactic acid to the product field using general plastics (based on petroleum resins), such as food packaging materials and containers and electronic product shells.

[0005] However, polylactic acid has lower impact resistance and heat resistance than conventional petroleum-based resins, and thus its application range is limited. In addition, the tensile strength is poor, and transparency is required depending on the application field, but the physical properties of polylactic acid are difficult to adjust, and it has limitations as a general-purpose resin.

[0006] In order to improve the above disadvantages, copolymers containing other repeating units in polylactic acid have been studied, and in particular, 3-hydroxypropionic acid has attracted attention as a comonomer. However, depending on the degree of introduction of 3-hydroxypropionic acid, the expressed physical properties appear different, and if the introduction degree is not adjusted, the inherent properties of polylactic acid may be damaged. Summary of the invention

[0007] Technical issues

[0008] An object of the present disclosure is to provide a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition having excellent transparency and a film including the same.

[0009] Technical Solution

[0010] According to one embodiment of the present disclosure, there is provided a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition, comprising: a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer and poly(3-hydroxypropionic acid), wherein the average haze measured by ASTM D1003 is less than 4.0.

[0011] According to another embodiment of the present disclosure, a film including the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition is provided.

[0012] Hereinafter, the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition and a film including the same according to specific embodiments of the present disclosure will be described in more detail.

[0013] Unless particularly mentioned herein, the term “include” or “comprising” means including any elements (or components) without any limitation, and should not be interpreted as excluding the addition of other elements (or components).

[0014] In addition, unless otherwise mentioned herein, the weight average molecular weight and number average molecular weight of poly (3-hydroxypropionic acid), poly (lactic acid-b-3-hydroxypropionic acid) block copolymer, etc. can be measured using gel permeation chromatography (gel permeation chromatography, GPC). Specifically, the polymer or copolymer is dissolved in chloroform to a concentration of 2mg / ml, and then 20 μL of the solution is injected into the GPC, and GPC analysis is performed at 40°C. At this time, chloroform is used as the mobile phase of GPC, with a flow rate of 1.0mL / min, and the column used is two Agilent Mixed-B units connected in series. RI detector is used as a detector. Mw values, etc. can be obtained using a calibration curve formed using a polystyrene standard sample. Twelve polystyrene standard samples having molecular weights of 162 g / mol, 580 g / mol, 1,180 g / mol, 4,870 g / mol, 9,310 g / mol, 17,120 g / mol, 75,050 g / mol, 200,500 g / mol, 448,500 g / mol, 10,690,000 g / mol, 3,022,000 g / mol, and 6,545,000 g / mol were used.

[0015] In the present disclosure, the haze may be a value measured by NDH5000W manufactured by Nippon Denshoku.

[0016] According to one embodiment of the present disclosure, there is provided a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition, comprising: a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer and poly(3-hydroxypropionic acid), wherein the average haze measured by ASTM D1003 is less than 4.0.

[0017] The present inventors have found that when a composition including a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer includes a predetermined amount of poly(3-hydroxypropionic acid) in addition to the block copolymer, the composition has an average haze of less than 4.0 and thus is excellent in physical properties such as transparency, and have completed the present disclosure.

[0018] Furthermore, a film including such a composition containing a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer also has excellent physical properties such as transparency, and thus can be applied to materials requiring transparency such as food packaging materials and optical films.

[0019] The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to one embodiment includes a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer and poly(3-hydroxypropionic acid).

[0020] The average haze of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition measured by ASTM D1003 may be less than 4.0, 3.9 or less, 3.8 or less, 0.5 or more, and 3.7 or less. If the average haze of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition is too high, there is a problem of not showing transparency.

[0021] Furthermore, the positional standard deviation of the haze value of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition may be 0.400 or less, 0.300 or less, or 0.100 or more and 0.250 or less.

[0022] The UV transmittance of poly (lactic acid-b-3-hydroxypropionic acid) block copolymer composition can be 80% or more, 82% or more, 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, 88% or more, 89% or more or 90% or more. In addition, the upper limit of UV transmittance is theoretically 100%, but can be, for example, 99.5% or less, 99.0% or less, 98.5% or less or 98.0% or less. UV transmittance can be measured by: the composition is produced into a film having a thickness of about 80 μm, which is then attached to a UV-visible spectrometer (Agilent 8453), wherein the transmittance value in the 480nm region can be determined.

[0023] The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to one embodiment may contain poly(3-hydroxypropionic acid) in an amount greater than 0 wt% and 7.0 wt% or less, 1.0 wt% or more and 6.5 wt% or less, 2.0 wt% or more and 6.0 wt% or less, or 3.0 wt% or more and 6.0 wt% or less, based on 100 wt% of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition.

[0024] Since the poly(3-hydroxypropionic acid) is included in a predetermined amount relative to the total content of 100 wt % of the composition, the composition appears to have a low average haze of less than 4.0 and can exhibit optical properties such as transparency. On the other hand, if the poly(3-hydroxypropionic acid) is included in an excessively large amount, there is a problem of accelerated crystallization due to phase separation and increased average haze, resulting in opacity.

[0025] The “poly(3-hydroxypropionic acid)” includes a repeating unit derived from 3-hydroxypropionic acid, and may include a repeating unit represented by the following Chemical Formula 2.

[0026] [Chemical formula 2]

[0027]

[0028] The poly(3-hydroxypropionic acid) can be subjected to the ring-opening polymerization with lactide described below to prepare the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer. Therefore, the poly(3-hydroxypropionic acid) contained in the composition can be a poly(3-hydroxypropionic acid) introduced into a reactor to prepare a block copolymer but remaining in the composition without reacting with lactide. Since the content of the poly(3-hydroxypropionic acid) remaining in the composition satisfies the above range, the composition can have excellent optical properties such as transparency.

[0029] In addition, the poly(3-hydroxypropionic acid) included in the composition may be poly(3-hydroxypropionic acid) for further mixing with the block copolymer after preparing the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer by ring-opening polymerization.

[0030] Therefore, the content of poly(3-hydroxypropionic acid) contained in the composition may be the sum of the content of residual poly(3-hydroxypropionic acid) that has not reacted with lactide and the content of residual poly(3-hydroxypropionic acid) added for further mixing with the block copolymer.

[0031] Meanwhile, the content of poly(3-hydroxypropionic acid) contained in the composition, especially the content of residual poly(3-hydroxypropionic acid) that has not reacted with lactide, can be controlled by the ratio of vinyl groups in the terminal groups of poly(3-hydroxypropionic acid), the number average molecular weight, etc.

[0032] The ratio of vinyl in the end group of the poly(3-hydroxypropionic acid) contained in the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to one embodiment may be 40 mol% or less, 35 mol% or less and 1 mol% or more, 30 mol% or less and 2 mol% or more, or 25 mol% or less and 3 mol% or more. If the ratio of vinyl in the end group of the poly(3-hydroxypropionic acid) is too high, the chain extension of the poly(3-hydroxypropionic acid) cannot occur well, and therefore, when the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer is prepared using the poly(3-hydroxypropionic acid), a large amount of unreacted poly(3-hydroxypropionic acid) remains, and the optical properties of the composition comprising the block copolymer, such as transparency, may deteriorate.

[0033] The vinyl group is generated by a side reaction occurring during the polymerization of 3-hydroxypropionic acid into poly(3-hydroxypropionic acid), and acts as a factor that destroys the equivalent ratio in polycondensation (where the equivalent ratio of each functional group (hydroxyl group, carboxyl group) is important), thereby inhibiting the reaction rate and making it difficult to obtain a polymer having a high molecular weight. In addition, if the vinyl group is present in poly(3-hydroxypropionic acid), there is a problem that chain extension of the poly(3-hydroxypropionic acid) by further modification does not occur well. Therefore, since poly(3-hydroxypropionic acid) has a small amount of vinyl group at the terminal group, it has the advantage of fundamentally reducing the above-mentioned disadvantages.

[0034] Poly(3-hydroxypropionic acid) can be prepared by condensation polymerization of 3-hydroxypropionic acid under specific conditions so that poly(3-hydroxypropionic acid) having a low ratio of vinyl groups in the terminal groups can be prepared. For example, poly(3-hydroxypropionic acid) having a low ratio of vinyl groups can be prepared by controlling the polymerization temperature.

[0035] The ratio of the end groups of poly(3-hydroxypropionic acid) can be determined using a Buker 500 MHz NMR model apparatus. 1 H-NMR measurement is used to calculate the ratio of vinyl groups to the total terminal groups. For example, the polymer is dissolved in d-CDCl3 at a concentration of 8 mg / ml, measured, and the ratio can be calculated according to the following mathematical equation 1.

[0036] [Mathematical equation 1]

[0037]

[0038] In mathematical equation 1,

[0039] a is the area value of 1H of C=C at 6.3 ppm, and

[0040] b is the area value of 2H of HO-CH2- at 3.8 ppm.

[0041] In addition, the number average molecular weight of the poly(3-hydroxypropionic acid) may be 5,000 or more and 300,000 or less, 7,000 or more and 250,000 or less, 8,000 or more and 200,000 or less, 9,000 or more and 180,000 or less, or 10,000 or more and 150,000 or less.

[0042] In addition, the weight average molecular weight of the poly(3-hydroxypropionic acid) can be 16,000 or more, 17,000 or more, 18,000 or more, 19,000 or more, or 20,000 or more, and 400,000 or less, 350,000 or less, 300,000 or less, 250,000 or less, 230,000 or less, 200,000 or less, 190,000 or less, 180,000 or less, 170,000 or less, or 60,000 or less.

[0043] If the number average molecular weight and / or the weight average molecular weight of the poly(3-hydroxypropionic acid) is too low, the effect of improving physical properties that the poly(3-hydroxypropionic acid) can impart may be reduced, whereas if the number average molecular weight and / or the weight average molecular weight is too high, thermal decomposition may occur during the ring-opening polymerization process, thereby possibly causing the formation of a vinyl group and reducing reactivity.

[0044] In addition, the molecular weight distribution (Mw / Mn) of the poly(3-hydroxypropionic acid) may be 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, or 2.0 or more, and 3.4 or less, 3.3 or less, 3.2 or less, or 3.1 or less.

[0045] The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer may be a block copolymer in which lactide is subjected to ring-opening polymerization in poly(3-hydroxypropionic acid). Poly(lactic acid-b-3-hydroxypropionic acid) exhibits excellent tensile strength and elastic modulus properties of the polylactic acid block, and the poly(3-hydroxypropionic acid) block reduces the glass transition temperature (Tg), increases flexibility, and improves mechanical properties such as impact strength, thereby preventing the polylactic acid from having poor elongation and easily exhibiting brittle properties.

[0046] Such block copolymer refers to a poly(3-hydroxypropionic acid)-poly(lactic acid) block copolymer comprising poly(lactic acid) repeating units and poly(3-hydroxypropionic acid) repeating units. The polymer category referred to as "poly(lactic acid-b-3-hydroxypropionic acid) block copolymer" can include all polymers obtained after completing the ring-opening polymerization and the repeating unit formation process, for example, unpurified or purified polymers obtained after completing the ring-opening polymerization, polymers contained in liquid or solid resin compositions before product formation, polymers contained in plastics or textiles after product formation, etc.

[0047] Poly(3-hydroxypropionic acid) has a structure in which a hydroxyl group, a carboxyl group, or a vinyl group may be present at the terminal as described above, and when the hydroxyl group and / or alkoxy group as the terminal of poly(3-hydroxypropionic acid) is added to the ring-opening polymerization reaction of the lactide monomer, the lactide monomer begins to be inserted from the terminal, and thus a block copolymer can be prepared. Therefore, if the content of the vinyl group in the terminal group of poly(3-hydroxypropionic acid) is increased, the ring-opening polymerization with lactide becomes difficult, and a large amount of residual lactide and poly(3-hydroxypropionic acid) is generated, which may cause the physical properties of the composition, such as optical properties, to deteriorate.

[0048] Meanwhile, poly(3-hydroxypropionic acid) is used as a polymerization initiator and is simultaneously included as a repeating unit in the block copolymer, thereby making it possible to improve mechanical properties such as flexibility and impact strength of the finally prepared block copolymer.

[0049] The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer may be represented by Chemical Formula 1 below.

[0050] [Chemical formula 1]

[0051]

[0052] Wherein in Chemical Formula 1,

[0053] m is an integer from 100 to 1000, and

[0054] n is an integer from 500 to 4000.

[0055] m may be 120 to 350. m means the number of repetitions of the monomer derived from 3-hydroxypropionic acid, and since it is introduced within the above range, physical properties such as transparency can be adjusted while maintaining the inherent physical properties of polylactic acid. More preferably, m may be 130 or more, 140 or more, 150 or more, 160 or more, 170 or more, 180 or more, 190 or more, or 200 or more; and 340 or less, 330 or less, 320 or less, 310 or less, or 300 or less.

[0056] n may be from 1000 to 2500. n means the number of repetitions of the monomer derived from lactide. More preferably, n may be 1100 or more, 1200 or more, 130 or more, 1400 or more, or 1500 or more; and 2400 or less, 2300 or less, 2200 or less, 2100 or less, or 2000 or less.

[0057] In addition, the relative ratio (m / n) of the monomer can be 0.05 to 0.20. Within the range of this m / n, physical properties such as transparency can be adjusted while maintaining the inherent physical properties of polylactic acid. More preferably, m / n can be 0.06 or more, 0.07 or more, or 0.08 or more; and 0.19 or less, 0.18 or less, 0.17 or less, 0.16 or less, or 0.15 or less. When poly (3-hydroxypropionic acid) is included in polylactic acid in too small an amount, brittleness may be larger, and when poly (3-hydroxypropionic acid) is included in polylactic acid in too large an amount, molecular weight may be reduced, and processability and heat resistance stability may be deteriorated.

[0058] A poly (lactic acid-b-3-hydroxypropionic acid) block copolymer composition, wherein:

[0059] The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer contains a poly(3-hydroxypropionic acid) block, and the poly(3-hydroxypropionic acid) block is contained in an amount of 1 wt% or more and 9 wt% or less based on 100 wt% of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition.

[0060] The weight average molecular weight (Mw) of poly (lactic acid-b-3-hydroxypropionic acid) block copolymer as measured using gel permeation chromatography (GPC) is 50,000 g / mol to 600,000 g / mol. More specifically, its weight average molecular weight is 50,000 g / mol or more, 70,000 g / mol or more, or 100,000 g / mol or more, and 550,000 g / mol or less, 500,000 g / mol or less, 450,000 g / mol or less, 300,000 g / mol or less, 250,000 g / mol or less, 200,000 g / mol or less, or 150,000 g / mol or less. If the weight average molecular weight of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer is too small, overall mechanical properties may be significantly deteriorated, whereas if the weight average molecular weight is too large, the process step may be difficult, and processability and elongation may be reduced.

[0061] The number average molecular weight (Mn) of poly (lactic acid-b-3-hydroxypropionic acid) block copolymer as measured using gel permeation chromatography (GPC) is 5,000 g / mol to 400,000 g / mol. More specifically, its number average molecular weight is 5,000 g / mol or more, 10,000 g / mol or more, or 20,000 g / mol or more, and 350,000 g / mol or less, 300,000 g / mol or less, 250,000 g / mol or less, 200,000 g / mol or less, 150,000 g / mol or less, 100,000 g / mol or less, or 90,000 g / mol or less, or 80,000 g / mol or less. If the number average molecular weight of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer is too small, overall mechanical properties may be significantly deteriorated, whereas if the number average molecular weight is too large, the process step may be difficult, and processability and elongation may be reduced.

[0062] The polydispersity index (PDI) of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer is 0.5 to 10.0, more specifically, 0.5 or more, 1.0 or more, 2.0 or more, 3.0 or more, or 4.0 or more, and 10.0 or less, 8.0 or less, 6.0 or less, or 5.0 or less.

[0063] The method for preparing a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition may include the steps of polymerizing 3-hydroxypropionic acid to prepare poly(3-hydroxypropionic acid); and subjecting lactide to ring-opening polymerization in poly(3-hydroxypropionic acid) to prepare a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer.

[0064] For example, the step of preparing poly(3-hydroxypropionic acid) may include the step of polymerizing 3-hydroxypropionic acid to prepare poly(3-hydroxypropionic acid).

[0065] The reaction temperature of the polymerization may be 70° C. to 120° C., and may be 72° C. or higher, 74° C. or higher, 76° C. or higher, 78° C. or higher, or 80° C. or higher, and 115° C. or lower, 110° C. or lower, 105° C. or lower, 100° C. or lower, or 95° C. or lower. In addition, the reaction pressure of the polymerization may be a pressure of 0.5 torr to 10 torr, for example, 0.6 torr or higher, 0.7 torr or higher, 0.8 torr or higher, or 1.0 torr or higher, and 9 torr or lower, 8 torr or lower, 7 torr or lower, 6 torr or lower, or 5 torr or lower. The reaction time of the polymerization can be appropriately determined in consideration of the molecular weight, yield, etc. of the produced 3-hydroxypropionic acid oligomer, and preferably, the polymerization can be carried out for 1 hour to 30 hours, for example, 2 hours or longer, 5 hours or longer, 6 hours or longer, 7 hours or longer, or 8 hours or longer, and 25 hours or shorter, 23 hours or shorter, 20 hours or shorter, 15 hours or shorter, or 10 hours or shorter.

[0066] The polymerization can be carried out in the presence of a sulfonic acid catalyst, wherein the sulfonic acid catalyst can be p-toluenesulfonic acid, m-xylene-4-sulfonic acid, 2-mesitylenesulfonic acid, or p-xylene-2-sulfonic acid. The catalyst can be used in an amount of 0.1 mol% to 0.5 mol%, 0.15 mol% to 0.4 mol%, or 0.2 mol% to 0.3 mol% relative to 3-hydroxypropionic acid.

[0067] The polymerization conditions can control the content of vinyl groups contained in the end groups of the produced poly(3-hydroxypropionic acid). For example, the vinyl content of the poly(3-hydroxypropionic acid) can be reduced by adjusting the polymerization reaction temperature, reaction pressure, reaction time and catalyst amount, for example, by controlling the conditions, such as lowering the polymerization reaction temperature, shortening the reaction time as much as possible and reducing the amount of catalyst used.

[0068] After the poly(3-hydroxypropionic acid) is prepared, the poly(3-hydroxypropionic acid), lactide, and a catalyst may be polymerized to prepare a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer.

[0069] Since the polymerization involves a lactide ring-opening polymerization reaction, it can be carried out in the presence of a lactide ring-opening catalyst. The catalyst used for the ring-opening polymerization can be any catalyst commonly used to produce polylactide resins by ring-opening polymerization of lactide monomers. For example, the ring-opening polymerization can be carried out under at least one catalyst selected from an organic metal complex catalyst and an organic catalyst. An organic metal complex catalyst can be used without limitation in its composition, as long as it is commonly used to prepare polylactide resins by ring-opening polymerization of lactide monomers. For example, the organic metal complex catalyst can be a catalyst represented by the following chemical formula 3.

[0070] [Chemical formula 3]

[0071] MA 1 p A 2 2-p

[0072] Wherein in Chemical Formula 1, M is Al, Mg, Zn, Ca, Sn, Fe, Y, Sm, Lu, Ti or Zr, p is an integer from 0 to 2, and A 1 and A 2 Each is independently an alkoxy group or a carboxyl group.

[0073] More specifically, the catalyst may be tin(II) 2-ethylhexanoate (Sn(Oct)2; hereinafter, also referred to as tin octoate).

[0074] On the other hand, an organic catalyst can be used without limitation in its composition, as long as it is generally used for preparing polylactide resin by ring-opening polymerization of lactide monomer. For example, the organic catalyst can be at least one selected from the following: 1,5,7-triazabicyclo-[4,4,0]dec-5-ene (TBD), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD), 4-dimethylaminopyridine (DMAP), 4-(1-pyrrolidinyl)pyridine (PPY), imidazole, triazole Thiourea, tertiary amines and creatinine.

[0075] Relative to 100mol% of lactide monomer, the content of the catalyst may be 0.0001mol% to 10mol%, 0.005mol% to 8mol%, 0.05mol% to 5mol%, or 0.09mol% to 3mol%. If the content of the catalyst is too low relative to 100mol% of lactide monomer, the polymerization activity may be insufficient, and if the content of the catalyst is too high, the amount of residual catalyst in the prepared block copolymer becomes larger, which may cause the copolymer to decompose or the molecular weight to decrease due to depolymerization such as transesterification reaction. In addition, the ring-opening polymerization can be carried out at 150°C to 200°C for 5 minutes to 24 hours.

[0076] According to another embodiment of the present disclosure, a film including the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition is provided.

[0077] The average haze measured by ASTM D1003 of the film comprising the poly (lactic acid-b-3-hydroxypropionic acid) block copolymer composition can be less than 4.0, 3.8 or less, 3.6 or less, or 0.5 to 3.4. If the average haze of the film is too high, there is a problem of not showing transparency. In addition, the position standard deviation of the haze value of the film can be 0.400 or less, 0.300 or less, or 0.100 or more and 0.200 or less.

[0078] In addition, the thickness of the film can be 500 μm or less, such as 10 μm or more, 30 μm or more, 50 μm or more, 70 μm or more, 90 μm or more, 100 μm or more, 120 μm or more, 140 μm or more, 150 μm or more, and 480 μm or less, 460 μm or less, 450 μm or less, 430 μm or less, 400 μm or less, 380 μm or less, 350 μm or less, 330 μm or less, or 300 μm or less. Due to the thickness of the film in the above range, the film has strong elasticity, excellent operability and good roll winding state or unfolding characteristics. In addition, within this thickness range, the film can show an average haze measured by ASTM D1003 less than 4.0.

[0079] Beneficial Effects

[0080] According to the present disclosure, a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition having excellent transparency and a film including the same may be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 It is a figure which shows the result of gel permeation chromatography analysis of an Example and a comparative example. DETAILED DESCRIPTION

[0082] Hereinafter, the present disclosure will be described in more detail by way of examples. However, the following examples are for illustrative purposes only, and the contents of the present invention are not thereby limited.

[0083] Preparation Example 1: Preparation of poly (3-hydroxypropionic acid) A

[0084] 50ml 60% 3-hydroxypropionic acid aqueous solution is placed in a 100ml Schlenk flask in an oil bath, and about 60% of the water in 3-hydroxypropionic acid is removed at 105°C and 50 torr for 2 hours. Subsequently, based on 100 parts by weight of 3-hydroxypropionic acid, 0.4 parts by weight of p-toluenesulfonic acid (p-TSA) catalyst and 0.1 parts by weight of tin octoate are placed in a reaction flask, and melt polycondensation is carried out at 80°C and 1 torr for 18 hours. After the reaction is complete, the reactant is dissolved in chloroform at a ratio of 10g / 50mL, and then extracted with 500mL of methanol to obtain poly(3-hydroxypropionic acid) A (ratio (content) of vinyl in the end group: 3mol%, number average molecular weight: 10,000g / mol, weight average molecular weight: 18,600g / mol).

[0085] Preparation Example 2: Preparation of poly (3-hydroxypropionic acid) B

[0086] 50ml 60% 3-hydroxypropionic acid aqueous solution is placed in a 100ml Schlenk flask in an oil bath, and about 40% of the water in the 3-hydroxypropionic acid is removed at 105°C and 50 torr for 2 hours. Subsequently, based on 100 parts by weight of 3-hydroxypropionic acid, 0.1 parts by weight of p-toluenesulfonic acid (p-TSA) catalyst is placed in a reaction flask, and melt polycondensation is carried out at 95°C and 1 torr for 24 hours. After the reaction is completed, the reactant is dissolved in chloroform at a ratio of 10g / 50mL, and then extracted with 500mL methanol to obtain poly(3-hydroxypropionic acid) B (ratio (content) of vinyl in the end group: 10mol%, number average molecular weight: 10,000g / mol, weight average molecular weight: 17,600g / mol).

[0087] Preparation Example 3: Preparation of poly (3-hydroxypropionic acid) C

[0088] 50ml of 60% 3-hydroxypropionic acid aqueous solution was placed in a 100ml Schlenk flask in an oil bath, and about 60% of the water in the 3-hydroxypropionic acid was removed at 105°C and 50 torr for 2 hours. Subsequently, based on 100 parts by weight of 3-hydroxypropionic acid, 0.4 parts by weight of p-toluenesulfonic acid (p-TSA) catalyst was placed in a reaction flask, and melt polycondensation was carried out at 105°C and 1 torr for 8 hours. After the reaction was completed, the reactant was dissolved in chloroform at a ratio of 10g / 50mL, and then extracted with 500mL of methanol to obtain poly(3-hydroxypropionic acid) C (ratio (content) of vinyl in the end group: 22mol%, number average molecular weight: 10,000g / mol, weight average molecular weight: 17,600g / mol).

[0089] Preparation Example 4: Preparation of poly(3-hydroxypropionic acid) D

[0090] 50ml 60% 3-hydroxypropionic acid aqueous solution is placed in a 100ml Schlenk flask in an oil bath, and about 60% of the water in 3-hydroxypropionic acid is removed at 105°C and 50 torr for 2 hours. Subsequently, based on 100 parts by weight of 3-hydroxypropionic acid, 0.2 parts by weight of p-toluenesulfonic acid (p-TSA) catalyst is placed in a reaction flask, and melt polycondensation is carried out at 95°C and 1 torr for 24 hours. After the reaction is complete, the reactant is dissolved in chloroform at a ratio of 10g / 50mL, and then extracted with 500mL methanol to obtain poly(3-hydroxypropionic acid) D (ratio (content) of vinyl in the end group: 30mol%, number average molecular weight: 10,000g / mol, weight average molecular weight: 21,100g / mol).

[0091] Preparation Example 5: Preparation of poly (3-hydroxypropionic acid) E

[0092] 50ml 60% 3-hydroxypropionic acid aqueous solution is placed in a 100ml Schlenk flask in an oil bath, and about 60% of the water in the 3-hydroxypropionic acid is removed at 105°C and 50 torr for 2 hours. Subsequently, based on 100 parts by weight of 3-hydroxypropionic acid, 0.4 parts by weight of p-toluenesulfonic acid (p-TSA) catalyst is placed in a reaction flask, and melt polycondensation is carried out at 95°C and 1 torr for 24 hours. After the reaction is completed, the reactant is dissolved in chloroform at a ratio of 10g / 50mL, and then extracted with 500mL methanol to obtain poly(3-hydroxypropionic acid) E (ratio (content) of vinyl in the end group: 44mol%, number average molecular weight: 10,000g / mol, weight average molecular weight: 16,400g / mol).

[0093] Preparation Example 6: Preparation of poly (3-hydroxypropionic acid) F

[0094] 50ml of 60% 3-hydroxypropionic acid aqueous solution was placed in a 100ml Schlenk flask in an oil bath, and about 60% of the water in the 3-hydroxypropionic acid was removed at 105°C and 50 torr for 2 hours. Subsequently, based on 100 parts by weight of 3-hydroxypropionic acid, 0.4 parts by weight of p-toluenesulfonic acid (p-TSA) catalyst was placed in a reaction flask, and melt polycondensation was carried out at 105°C and 1 torr for 24 hours. After the reaction was completed, the reactant was dissolved in chloroform at a ratio of 10g / 50mL, and then extracted with 500mL of methanol to obtain poly(3-hydroxypropionic acid) F (ratio (content) of vinyl in the end group: 72mol%, number average molecular weight: 10,000g / mol, weight average molecular weight: 17,100g / mol).

[0095] Example 1: Preparation of block copolymer

[0096] 20 g of lactide, 2 g of poly(3-hydroxypropionic acid) A prepared in Preparation Example 1 and 0.009 mL of tin(II) 2-ethylhexanoate were placed in a 100 mL Schlenk flask and dried in a vacuum at 40° C. and 1 torr for 5 hours. Subsequently, the mixture was placed in an oil bath preheated to 180° C. and subjected to polymerization for 1 hour and 30 minutes to prepare a poly(lactic acid-b-3-hydroxypropionic acid) block copolymer (weight average molecular weight: 128,600 g / mol, number average molecular weight: 50,700 g / mol, polydispersity index (PDI): 2.5). The block copolymer was then recovered from the oil bath and devolatilized at 140° C. under reduced pressure of 1 torr to 5 torr for 3 hours to remove the monomer.

[0097] Example 2: Preparation of block copolymers

[0098] A poly(lactic acid-b-3-hydroxypropionic acid) block copolymer (weight average molecular weight: 95,500 g / mol, number average molecular weight: 31,100 g / mol, polydispersity index (PDI): 3.1) was prepared in the same manner as in Example 1, except that poly(3-hydroxypropionic acid) B prepared in Preparation Example 2 was used instead of poly(3-hydroxypropionic acid) A.

[0099] Example 3: Preparation of block copolymers

[0100] A poly(lactic acid-b-3-hydroxypropionic acid) block copolymer (weight average molecular weight: 87,100 g / mol, number average molecular weight: 31,200 g / mol, polydispersity index (PDI): 2.8) was prepared in the same manner as in Example 1, except that 4 g of poly(3-hydroxypropionic acid) B prepared in Preparation Example 2 was used instead of 2 g of poly(3-hydroxypropionic acid) A.

[0101] Example 4: Preparation of block copolymers

[0102] A poly(lactic acid-b-3-hydroxypropionic acid) block copolymer (weight average molecular weight: 119,800 g / mol, number average molecular weight: 44,440 g / mol, polydispersity index (PDI): 2.7) was prepared in the same manner as in Example 1, except that poly(3-hydroxypropionic acid) C prepared in Preparation Example 3 was used instead of poly(3-hydroxypropionic acid) A.

[0103] Example 5: Preparation of block copolymers

[0104] A poly(lactic acid-b-3-hydroxypropionic acid) block copolymer (weight average molecular weight: 115,200 g / mol, number average molecular weight: 37,200 g / mol, polydispersity index (PDI): 3.1) was prepared in the same manner as in Example 1, except that poly(3-hydroxypropionic acid) D prepared in Preparation Example 4 was used instead of poly(3-hydroxypropionic acid) A.

[0105] Comparative Example 1: Preparation of block copolymer

[0106] A poly(lactic acid-b-3-hydroxypropionic acid) block copolymer (weight average molecular weight: 103,400 g / mol, number average molecular weight: 42,600 g / mol, polydispersity index (PDI): 2.4) was prepared in the same manner as in Example 1, except that poly(3-hydroxypropionic acid) E prepared in Preparation Example 5 was used instead of poly(3-hydroxypropionic acid) A.

[0107] Comparative Example 2: Preparation of block copolymer

[0108] A poly(lactic acid-b-3-hydroxypropionic acid) block copolymer (weight average molecular weight: 113,800 g / mol, number average molecular weight: 31,900 g / mol, polydispersity index (PDI): 3.6) was prepared in the same manner as in Example 1, except that poly(3-hydroxypropionic acid) F prepared in Preparation Example 6 was used instead of poly(3-hydroxypropionic acid) A.

[0109] Comparative Example 3: Preparation of polymer blends

[0110] (1) Preparation of polylactic acid

[0111] 20g lactide, 2μl 1-octanol and 0.002mL 2-ethylhexanoic acid tin (II) were placed in a 100ml Schlenk flask and dried for 5 hours at 40°C and 1 torr in a vacuum. Subsequently, the mixture was placed in an oil bath preheated to 180°C and polymerized for 1 hour and 30 minutes to prepare polylactic acid (weight average molecular weight: 18,000g / mol). The block copolymer was then recovered from the oil bath and devolatilized at 140°C under a reduced pressure of 1 torr to 5 torr for 3 hours to remove the monomer.

[0112] (2) Preparation of polymer blends

[0113] 100 wt % of polylactic acid and 5 wt % of poly(3-hydroxypropionic acid) B prepared in Preparation Example 2 were placed in a screw extruder (Thermo Scientific, MiniCTW), and extruded and mixed at 190° C. to prepare a polymer blend.

[0114] Comparative Example 4: Preparation of polymer blends

[0115] A polymer blend was prepared in the same manner as in Comparative Example 3, except that 10 wt% of poly(3-hydroxypropionic acid) B was used instead of 5 wt% of poly(3-hydroxypropionic acid) B.

[0116] Evaluate

[0117] 1. Gel Permeation Chromatography (GPC) Analysis

[0118] The products obtained from the Examples and Comparative Examples were analyzed by GPC to measure the molecular weight of the block copolymer, and the results are shown in Table 1 below. Then, the products were analyzed by GPC-IR to measure the content of poly(3-hydroxypropionic acid) contained in the products, and the results are shown as "P(3HP) content X" in Table 1 below.

[0119] <GPC Analysis Conditions>

[0120] The product was dissolved in chloroform to a concentration of 2 mg / ml, and then 20 μl of the solution was injected into the GPC, and GPC analysis was performed at 40 °C. At this time, chloroform was used as the mobile phase of the GPC, the flow rate was 1.0 mL / minute, and the columns used were two Agilent Mixed-B units connected in series. An RI detector was used as the detector. The Mw value was obtained using a calibration curve formed with a polystyrene standard sample. Twelve polystyrene standard samples with molecular weights of 162 g / mol, 580 g / mol, 1,180 g / mol, 4,870 g / mol, 9,310 g / mol, 17,120 g / mol, 75,050 g / mol, 200,500 g / mol, 448,500 g / mol, 10,690,000 g / mol, 3,022,000 g / mol, and 6,545,000 g / mol were used.

[0121] 2. Nuclear Magnetic Resonance (NMR) Analysis

[0122] The products obtained from the Examples and Comparative Examples were analyzed by NMR, and the total content of "poly(3-hydroxypropionic acid)" contained in the products and "poly(3-hydroxypropionic acid) block" contained in the block copolymer was measured, and the results are shown as "Total P(3HP) content (X+Y)" in Table 1 below. On the other hand, the content of "poly(3-hydroxypropionic acid) block" was calculated as the difference between "Total P(3HP) content (X+Y)" and "P(3HP) content X", and the results are shown as "P(3HP) block content Y" in Table 1 below.

[0123] <NMR Analysis Conditions>

[0124] Sample pretreatment: 10 mg of sample was dissolved in 1 mL of chloroform and then applied for analysis.

[0125] 1 H solution NMR

[0126] Pulse program: zg30

[0127] Ns: 16

[0128] d1: 10 seconds

[0129] Temperature: 298K

[0130] 3. Haze measurement

[0131] The hot press obtained from the examples and comparative examples was used to manufacture a film having a thickness of 0.3T (300 μm). The SPL was collected at the center of each roller at 0 m, 200 m, 400 m, 600 m, 800 m and 1000 m from the starting point of the roller using a haze meter (Nippon Denshoku NDH5000W), and the haze value of the film was measured by the ASTM D1003 method. The average value and standard deviation were calculated and are shown in Table 1 below.

[0132] [Table 1]

[0133]

[0134] -P(3HP): Poly(3-hydroxypropionic acid)

[0135] According to Table 1, it was determined that in Examples 1 to 5, the content (X) of poly(3-hydroxypropionic acid) contained in the composition was 3.0 wt % to 7.0 wt %, and the average haze of the film produced therefrom was 3.7 or less, which showed excellent transparency characteristics.

[0136] On the other hand, it was determined that in Comparative Examples 1 and 2, the content (X) of poly(3-hydroxypropionic acid) contained in the composition was 7.7 wt% and 9.0 wt%, respectively, and the average haze of the films produced therefrom was 4.0 or greater, which showed transparency characteristics lower than those of the embodiments.

[0137] In addition, it was determined that the films produced from the compositions of Comparative Examples 3 and 4 (which were polymer blends) had a significantly high haze of 5.3 or more, and in the case of Comparative Example 4 in which the content (X) of poly(3-hydroxypropionic acid) was 10.0 wt %, the average haze was 31.2, which showed high opacity.

Claims

1. A poly (lactic acid-b-3-hydroxypropionic acid) block copolymer composition, comprising: Poly(lactic acid-b-3-hydroxypropionic acid) block copolymer and poly(3-hydroxypropionic acid), The average haze measured by ASTM D1003 is less than 4.

0.

2. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1, wherein: The poly(lactic acid-b-3-hydroxypropionic acid) is included in an amount of greater than 0 wt% and 7.0 wt% or less, based on 100 wt% of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition.

3. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1, wherein: The poly(lactic acid-b-3-hydroxypropionic acid) is included in an amount of 3.0 wt% or more and 6.0 wt% or less, based on 100 wt% of the poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition.

4. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1, wherein: The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer is a block copolymer in which lactide is subjected to ring-opening polymerization in poly(3-hydroxypropionic acid).

5. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1 or 4, wherein: The ratio of vinyl groups in the terminal groups of the poly(3-hydroxypropionic acid) is 40 mol% or less.

6. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1 or 4, wherein: The poly(3-hydroxypropionic acid) has a number average molecular weight of 5,000 or more and 300,000 or less.

7. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1, wherein: The poly (lactic acid-b-3-hydroxypropionic acid) block copolymer is represented by the following Chemical Formula 1: [Chemical formula 1] Wherein in Chemical Formula 1, m is an integer from 100 to 1000, and n is an integer from 500 to 4000.

8. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1, wherein: The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer has a weight average molecular weight of 50,000 or more and 600,000 or less.

9. The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1, wherein: The poly(lactic acid-b-3-hydroxypropionic acid) block copolymer composition has a UV transmittance of 80% or more. 10 . A film comprising the poly (lactic acid-b-3-hydroxypropionic acid) block copolymer composition according to claim 1 .

11. The membrane of claim 10, wherein: The film has an average haze of less than 4.0 as measured by ASTM D1003.

12. The membrane of claim 11, wherein: The positional standard deviation of the haze value of the film is 0.400 or less.

13. The membrane of claim 10, wherein: The thickness of the film is 500 μm or less.